2019
DOI: 10.3390/s19010162
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Energy Consumption of Depth Tracking Control Based on Model Predictive Control for Autonomous Underwater Vehicles

Abstract: For long-term missions in complex seas, the onboard energy resources of autonomous underwater vehicles (AUVs) are limited. Thus, energy consumption reduction is an important aspect of the study of AUVs. This paper addresses energy consumption reduction using model predictive control (MPC) based on the state space model of AUVs for trajectory tracking control. Unlike the previous approaches, which use a cost function that consists of quadratic deviations of the predicted controlled output from the reference tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Comprehensively analyze the above two situations as shown in Equations (14) and (18), combined with the comparison principle of ordinary differential equations, it can be achieved that…”
Section: Of 26mentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensively analyze the above two situations as shown in Equations (14) and (18), combined with the comparison principle of ordinary differential equations, it can be achieved that…”
Section: Of 26mentioning
confidence: 99%
“…Hence, state constraints which may lead to control effect degradation, and even instability and actuator faults, should be given attention [17]. There have been various approaches to deal with state constraints, such as model predictive control [18], reference governors [19], etc. One of various efficient approaches is the barrier Lyapunov function (BLF)-based control scheme, in which the value of the function approximates infinity when its arguments approach the constraints [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Yao proposed an energy consumption reduction method based on MPC (model predictive control) with a quadratic energy consumption term added into the cost function for AUV's trajectory tracking control. e simulation results showed that the proposed MPC method is feasible and effective for energy consumption reduction of AUV even with great model uncertainty [20].…”
Section: Introductionmentioning
confidence: 96%
“…Controller design for AUVs has been a challenge because controllers are closely linked to AUV dynamics in complex underwater environments [9][10][11]. The AUV controller can consist of discrete models, continuous models, and their interaction in a hybrid dynamic system (HDS), as modeled by hybrid automata (HA) [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%